Energy Contagion Analysis: A New Perspective with Application to a Small Petroleum Economy - Scott M. R. Mahadeo; Reinhold Heinlein; Gabriella Deborah Legrenzi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We put forward the novel concept of energy contagion, i.e. a deepening of energy-finance linkages under crisis periods in energy markets, and test for this using standard correlation measures and recently proposed adjusted correlation, co-skewness, and co-volatility contagion tests. Our analysis is applied to the oil-exchange rate and oil-stock market relationships of the small petroleum economy of Trinidad and Tobago. By defining our samples for the contagion measures in terms of calm and crisis conditions in the international crude oil market, we are able to compare how various co-moments in the energy-finance nexus change during oil booms and slumps using semi-parametric rule-based algorithms, as well as during relatively tranquil and turbulent oil price volatility episodes with a non-hierarchical k-means clustering algorithm on volatility measures. Our main results show a negative oil-real effective exchange rate dependency; a weak oil-stock returns association; and the existence of several energy contagion channels in both financial relationships, which vanish when we control for the contemporary global financial crash. Energy contagion analysis is essential to financial stability analysis in economies where prosperity is linked to the prices of hard commodities.
Keywords: C58; Q49; 330; contagion; correlation; exchange rate; oil price; stock market; Trinidad and Tobago